2000
DOI: 10.1080/003655900750016869
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Stone Formers Treated with a Low Dose of Sodium Potassium Citrate

Abstract: We evaluated the clinical efficacy of long-term preventive treatment with a single evening dose of alkaline citrate. Information was collected from the files of 52 recurrent stone formers prescribed a daily intake of 3.75-5 g of sodium potassium citrate (SPC; 14-18 mmol of citrate). The annual and cumulative rates of stone formation and the rate of recurrence were compared before and during the treatment. A comparison was also made between the patients with (Group R) and without (Group NR) recurrent stone form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Both sodium potassium citrate and potassium citrate alter urinary composition favourably [63][64][65][66][67][68][69], but the admixture of sodium might result in an increased calcium excretion or a less pronounce reduction in urinary calcium [37,70]. Clinical studies subsequently indicated that potassium citrate is superior to sodium potassium citrate in counteracting stone formation [71].…”
Section: Alkaline Citratementioning
confidence: 99%
See 1 more Smart Citation
“…Both sodium potassium citrate and potassium citrate alter urinary composition favourably [63][64][65][66][67][68][69], but the admixture of sodium might result in an increased calcium excretion or a less pronounce reduction in urinary calcium [37,70]. Clinical studies subsequently indicated that potassium citrate is superior to sodium potassium citrate in counteracting stone formation [71].…”
Section: Alkaline Citratementioning
confidence: 99%
“…In the average population of recurrent stone formers the annual frequency of stone formation is <0.15-0.20 [35,36], thus no definite conclusions can be drawn from treatment periods of <5-7 years! To maintain patients on placebo treatment for so long is not easy, particularly as compliance even among patients given active medication is surprisingly low [37,38].…”
Section: Theoretical Possibilities For Preventing Recurrence In Patiementioning
confidence: 99%
“…Despite its proven efficacy, compliance with potassium citrate therapy is poor. In one study that looked at long-term follow-up of stone formers who were treated with potassium citrate, only 62% consistently took the medication [ 14 ]. In addition, given that potassium citrate therapy is costly, upward off $180 USD/month for three times daily dosing of 20 meq, alternative dietary therapies have been evaluated [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other data have suggested that patients taking citrate supplementation regress toward baseline stone risk as the interval from treatment initiation increases. 17 It is unclear whether this latter observation resulted from homeostatic conservation of body acid base status or poor long-term compliance. In any case, the relationship between urinary citrate and pH evidently is far from clear.…”
Section: Commentmentioning
confidence: 99%